Hubungan kadar leptin terhadap parameter trombosit pada pasien dengan obesitas - Dwi Fajaryani; Meita Hendrianingtyas; Dwi Retnoningrum (DiscoverSys Inc., 2019)
Background: Obesity is excessive and abnormal fat accumulation thus harmful to health. Increase in body mass index (BMI) in obesity, also accompanied by increase hormon which synthesized and released by adipose tissue informs the brain for controlling hunger and food intake that is Leptin. Leptin plays a role in chronic inflammatory process of obesity. Leptin receptor was detected in human platelets and high concentration of leptin reported to promote platelet aggregation. The platelet parameters examination is a cheap, easy, and routinly done in daily basis, which consist of platelet counts, mean platelet volume (MPV), platelet distribution width (PDW), platelet large cell ratio (PLCR), plateletcrit (PCT), which indicates platelet proliferation. The aim of research was to look the relationship of leptin with thrombocyte parameter in obesity people.Methods: Cross sectional study of 45 obese adults, based on RISKESDAS criteria with BMI>27, on Mei-September 2018 was done. Venous blood collected in EDTA and plain tube. The EDTA sample was used for complete hematological examination to obtain platelet parameters by Hematology analayzer with impendace method. Serum from plain tube used for leptin examination was measured by ELISA. Data were analyzed by Pearson and Spearman correlation test. P-value < 0,05 was consideres as significant.Results: There is no correlation between leptin and platelet count (r=0,051, p=0,740), MPV (r=0,021, p=0,891), PDW (r=-0,093, p=0,541), P-LCR (r=0,082, p=0,593), and PCT (r=0,079, p=0,605). Conclusion: There is no correlation between leptin and platelet parameters in obesity. Further studies need to be done with adding another characteristic such as inflammation markers, metabolic syndrome parameters and platelet activation